(untitled) (Canadian Medical Education Journal, 2020)
Introduction: We conducted a national survey to characterize current Canadian procedural skills training in Undergraduate Medical Education (UGME). The goals were to identify the most important procedures students should know upon graduation and assess clinician-educator perceptions regarding implementation of a pre-clerkship procedural program. Methods: We distributed the survey to physician-educators across Canada’s 17 medical schools. Respondents were directed to an individualized survey that collected demographic data, physician-educator responses on essential procedural skills, as well as physician-educator opinions on the value of a pre-clerkship procedural training program. Results: The response rate for this survey was 21% (42 out of 201 distributed surveys were completed). The top 10 most important procedures identified by physician-educators included IV Access, Airway Management, Local anesthesia/field block, Casting, Spontaneous Vaginal Delivery, Testing for STIs, Phlebotomy, Suturing of Lacerations, Nasogastric Tube Insertion, and Venipuncture. Physician-educators supported a pre-clerkship procedural program. Conclusions: Identifying the most crucial procedural skills is the first step in implementing a competency-based procedural skills training program for Canadian medical students. With the list of essential skills, and the support for physician-educators in developing a pre-clerkship procedural skills curriculum, hopefully there can be future development of formalized curricula.